Heptanickel(ii) double-cubane core in wells-dawson heteropolytungstate, [Ni7(OH)6(H2O)6(P2W15O56)2]16−. Issue 12 (11th January 2016) - Bassil, Bassem S.; Xiang, Yixian; Haider, Ali; Hurtado, Jaime; Novitchi, Ghenadie; Powell, Annie K.; Bossoh, A. Martin; Mbomekallé, Israël M.; de Oliveira, Pedro; Kortz, Ulrich
Abstract : We have prepared a ferromagnetic heptanickel(ii )-hydroxo core with a rare double-cubane arrangement inside a 30-tungsto-4-phosphate host, leading to a discrete, solution-stable assembly. Abstract : The hepta-Ni 2+ -containing 30-tungsto-4-phosphate(v ) [Ni7 (OH)6 (H2 O)6 (P2 W15 O56 )2 ] 16− (1) has been synthesized in aqueous, slightly basic medium under conventional reaction conditions, and charactarized via different physical methods. Single-crystal XRD showed that 1 consists of a corner-fused double-cubane Ni7 (OH)6 (H2 O)6 8+ fragment sandwiched by two trilacunary [P2 W15 O56 ] 12− units. Polyanion 1 is solution-stable as shown by 31 P NMR. Ferromagnetic coupling interaction between the 7 paramagnetic centers of the double-cubane core in 1 with a S = 7 ground state was demonstrated. Electrochemical studies were also performed on 1.